Research into complexing properties of polyacrylonitrile complexite in the mixtures of water-dioxane - Korovnikova, Natalia; Dubyna, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2017)
We studied complexing properties of a fibrous complexite based on polyacrylonitrile relative to copper(II) ions taking into consideration solvation parameters of polymer ligands in the mixed solvent of water-1.4-dioxane. The object was obtained through chemical modification of the industrial fiber nitron; it has in the grafted chains the complexing groups of amidoxime, hydroxamic acid and carboxylic groups. Complexation equilibria and stability of the complexes of copper(II) with the complexite were studied using the potentiometric titration methods, infrared spectroscopy, spectroscopy of diffuse reflection, swelling. Complexing properties of the polyacrylonitrile complexite have been identified relative to copper(II) ions in the mixtures of water-1.4-dioxane. Complexation takes place with the participation of hydroxamic groups of the polymer. In the range of pH 3.8‒6.2, along with hydroxamic groups, in the mixtures with a molar share of dioxane at 0.17 and 0.32, the formation of HMCC-Сu2+ involves amidoxime groups. The character of change in the stability constants of HMCC-Сu2+ with an increase in the content of dioxane is due to the structural characteristics of mixtures, particle over-solvation, restructuring of the coordination centers of HMCC by introducing to their coordination sphere the DO molecules, and reveals the essential role of specific solvation. It was found that solvation effects in the mixture of water-1.4-dioxane with a molar share of dioxane at 0.00‒0.17 reduce stability of the resulting complexes of HMCC-Сu2+. The biggest impact of solvation parameters of the complexite is achieved in the composition of mixture at 0.32.